Determination of maximal oxygen uptake through a new basketball-specific field test - Adsiz, E.; Nalcakan, G. R.; Varol, S. R.; Vural, F. (Baltic Journal of Health and Physical Activity, 2017)
Background: The aim of this study was to develop a new basketball-specific field test (BSFT) that determines the maximal oxygen uptake indirectly and to determine the reliability and validity of the test for measuring aerobic power. Material/Methods: An aerobic endurance-based test totalling 1.5 miles on a basketball court including side steps and running was designed to be completed as quickly as possible. 15-year-old, male basketball players` maximal oxygen uptake (VO2max) levels measured directly as the gold standard laboratory test. Results: Laboratory test results showed a significant negative correlation between the VO2max level and the duration of the BSFT (r = -0.705, p = 0.015). Regression analysis through the BSFT proved moderate validity (R2 = 0.390), and the following regression formula was then developed to estimate the VO2max level: 122.617-5.461×(BSFT duration). The reliability was evaluated by the test-retest method; there was no difference between the duration of the BSFT (p > 0.05) repeated at intervals, and this test showed high reliability (%CV:8.81 and ICC:0.90). Conclusions: The BSFT, which proved to be reliable and valid for measuring aerobic power indirectly, may be considered to help coaches and athletes by means of its properties that do not require expensive equipment and specialist staff and ensure easy and practical application by using simple basketball-specific movements on basketball courts.